FORMATION OF AESTHETIC CULTURE OF FUTURE TEACHER OF THE FOREIGN LANGUAGE - Sh.T. Khalilova; M.K. Fayziyeva (International Journal of Innovations in Engineering Research and Technology, 2021)
In this article are opened: a number of the features influencing process of formation of esthetic culture of future teacher of a foreign language, optimal conditions the providing success and efficiency of formation of esthetic culture of future teacher of a foreign language. The main stages of skilled and experimental work on formation of esthetic culture of future teacher of a foreign language, structure of creation of process of formation of esthetic culture of future teacher of a foreign language, and the recommendation about formation of esthetic culture of future teacher of a foreign language are offered: